2007
DOI: 10.1515/ijnsns.2007.8.3.329
|View full text |Cite
|
Sign up to set email alerts
|

An Improved 'Heuristic' Approximation for the Period of a Nonlinear Pendulum: Linear Analysis of a Classical Nonlinear Problem

Abstract: A new analytical approximate expression for the period of the simple pendulum is obtained by using a heuristic but pedagogical derivation. This formula depends on two parameters obtained by comparing term-by-term the power-series expansions of the approximate and exact expressions for the period. This formula is compared with others in the literature and the numerical results obtained show that the published approximations are not nearly as good as the new expression proposed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The homotopy perturbation method [14][15][16][17][18][19][20][21][22][23][24][25] is a general method for solving the differential and integral equations. This method is explained in references 7 and 8 for solving a nonlinear differential equation like Equation (14).…”
Section: Application Of Modified Homotopy Perturbation Methods For Solmentioning
confidence: 99%
See 2 more Smart Citations
“…The homotopy perturbation method [14][15][16][17][18][19][20][21][22][23][24][25] is a general method for solving the differential and integral equations. This method is explained in references 7 and 8 for solving a nonlinear differential equation like Equation (14).…”
Section: Application Of Modified Homotopy Perturbation Methods For Solmentioning
confidence: 99%
“…Substitution of the power series (19) and (20) into Equation (18), and collecting terms of the same power of , p gives the following set of linear equations: …”
Section: Application Of Modified Homotopy Perturbation Methods For Solmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very difficult to solve nonlinear problems and, in general, it is often more difficult to get an analytic approximation than a numerical one to a given nonlinear problem. There are several methods used to find approximate solutions to nonlinear problems, such as perturbation techniques [1][2][3][4][5][6][7], harmonic balance based methods [8][9][10][11][12] or other techniques [13][14][15][16][17][18]. An excellent review on some asymptotic methods for strongly nonlinear equations can be found in detail in references [19] and [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to solve nonlinear problems and, in general, it is often more difficult to get an analytic approximation than a numerical one for a given nonlinear problem. There are several methods used to find approximate solutions to nonlinear problems, such as perturbation techniques [1][2][3][4][5][6], harmonic balance based methods [6][7][8][9] or other techniques [10][11][12][13][14][15][16][17][18]. An excellent review on some asymptotic methods for strongly nonlinear equations can be found in detail in references [19] and [20].…”
Section: Introductionmentioning
confidence: 99%